Dynamics of External Structure of the Personality’s Speech Experience - Orap, Maryna (East European Journal of Psycholinguistics, 2014)
The paper is an attempt to describe the dynamic features of personality’s speech experience. The author theoretically substantiates the concept of personality’s speech experience system, viewed as the process and the product of processing and organizing speech, resulted from the interaction with the environment. This fact enables personal mastering of the world through speech. The article analyzes the results of the study the external structure of the speech experience in two age groups - children of primary school age (194 respondents) and the period of «early adulthood» (386 respondents) by the method of factor analysis. The basic meaning and interpretation of factors are given. Results of comparing the contents of the factors in the two age groups allow defining the dynamics of the external structure. The development of the external structure is going through integration - through the union of separate parts into a whole. These parts are not mechanically connected to each other, but dialectically changing, acquiring a new quality. Therefore, the six factors of the structures that were found in children of primary school age are different from the factors identified in adults. Generalization of individual parts gives rise to three factors in adulthood, which exhibits a clear focus on the mediation the personality’s speech mastering of the world. Thus, the dynamics of the external structure of the personality’s speech experience consists in the integration processes of hierarchization and articulation, which leads to the functioning the speech experience as optimally organized system. References Anokhin, P. (1978). Izbrannye Trudy. Filosofskie aspekty teorii funktsional’nykh sistem. [Selected Works. Philosophical Aspects of the Theory of Functional Systems]. Moscow: Nauka. Chomsky, N. (1993). Language and Thought. USA: MOYER BELL limited. Chepeleva, N.V. (2004). Problemy Psykhologіchnoyi Hermenevtyky [The problems of Psychological Hermeneutics]. Kyiv: Vyd-vo National Pedagogical University named after N.P.Dragomanov. Druzhinin, V. (1999). Psikhologiya Obshchikh Sposobnostey [Psychology of General Abilities]. S.-Petersburg: PITER. Kholodnaya, M. (2012). Psikhologiya Ponyatiynogo Myshleniya: Ot Kontseptual’nykh Struktur k Ponyatiynym Sposobnostyam [Psychology of Conceptual Thinking: From Conceptual Frameworks to Conceptual Abilities]. Moscow: Institute Psychology RAN. Laktionov, A. (2010). Koordinaty Individualnogo Opyta [Coordinates of Individual Experience]. Kharkiv: Kharkiv University. Leontyev, A. (1969). Yazyk, Rech, Rechevaya Deyatelnost’ [Language, Speech, Speech Activity]. Moscow: Prosvechenie. Neisser, U. (1976). Cognition and Reality: Principles and Implications of Cognitive Psychology. New York: Freeman. Orap, M. (2013). Teoretychnyi analіz kategorіyi “movlennevyi dosvіd osobystostі”. [Theoretical analysis of “individual speech experience” category). Humanіtarnyi Vіsnik of Hryhorіy Skovoroda Pereyaslav-Khmelnytskyi State Pedagogіcal University, 29, 272–278. Solso, R. (2001). Cognitive Psychology. 6 th ed. Boston: Allyn and Bacon. Pokhil’ko, V., Fedotova, O. (1984). Tekhnika repertuarnykh reshetok v eksperimental’noy psikhologii lichnosti [Repertory grid technique in experimental psychology of personality]. Voprosy Psikhologii. 3. 151–157. Zalevskaya, A. (2000). Vvedeniye v Psikholingvistiku [Introduction to Psycholinguistics]. Moscow: Russian State University for the Humanities. Zimnyaya, I. (1983). Psikhologicheskiye Aspekty Obucheniya Govoreniyu na Inostrannom Yazyke [Psychological Aspects of Teaching Foreign Language Speaking]. Moscow: Prosvechenie.